Kombinasi Metode Design Thinking Dan User-Centered Design Pada Perancangan UI/UX Aplikasi Bimbingan Konseling - Dina Juliarti; Angga Bayu Santoso (Institut Teknologi Garut, 2026)
Counseling Guidance (BK) services at SMA Global Madani have been constrained by an inefficient manual system for teachers and psychological barriers experienced by students. This study designs a mobile-based user interface and user experience prototype to optimize counseling guidance services. The methods used combine Design Thinking during the discovery stage and User-Centered Design (UCD) during the technical validation stage. Data were collected from 13 participants through interviews and questionnaires, which were then analyzed using Empathy Maps and User Personas. The testing results using the System Usability Scale (SUS) showed an average score of 84.80 (Grade B/Excellent), outperforming previous studies that used a single-method approach, which achieved a score of 74.37. Conceptually, this integration demonstrates that users’ emotional comfort is a crucial parameter in the effectiveness of sensitive digital services. This study contributes to the development model of educational information systems that position students as the primary subjects within the digital ecosystem.